IMPLEMENTATION OF CTL MODELS WITH PLASTISIN MEDIA TOWARDS COGNITIVE MAPPING OF STUDENTS IN BASIC SCHOOL LEARNING - Utaminingtyas, Siwi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Contextual learning (CTL) is a learning concept where the teacher presents the real world into the classroom and encourages students to make a connection between their knowledge and application in their daily lives, as a means to solve problems in everyday life. Learning with the CTL model opens the widest opportunity for students to empower themselves. Primary school children are the world of play, in the lives of children, most of their time is spent playing. Playing in learning provides an opportunity for children to express their creativity to find the use of things differently, find new relationships with one another. The use of plasticine as an IPS learning media can foster students' creativity in their learning, the game is more directed towards finding concept maps and interpreting the topic of existing learning material so as to foster learning motivation in achieving achievement.